POLITIK HUKUM PENDIDIKAN SEBUAH PROSES MULTIDIMENSI - Kushandajani S.H., M.H. (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2011)
Education is the most important for human being, because without it the human being can not achieve many things.UUD1945 said that education is one of the human right whereby state must fill it. Many legal policies about education are declared, for example Law No. 20 of 2003 and Law No. 14 of 2005, as a serious effort to make Indonesian educated people. But it must be realized that it was not adequate tool to see policy just from the law. It is needed contribution many sector eg: social, cultural, economics, and politics to develop great commitment and to make progress education.